Neutralizing and cross-reacting antibodies: implications for immunotherapy and SARS-CoV-2 vaccine development - Samuel A. Cohen; Caitlyn Kellogg; Ozlem Equils (Human Vaccines & Immunotherapeutics, 2021)
The novel coronavirus SARS-CoV-2 emerged in China in 2019 and quickly spread globally, causing a pandemic. There is an urgent need to develop vaccines against the virus, and both convalescent plasma and immune globulin are currently in clinical trials for treatment of patients with COVID-19. It is unclear whether antibodies induced by SARS-CoV-2 have neutralizing capacity and whether they can protect from future infection. Seasonal human coronaviruses (HCoV) have been circulating for decades. It is currently unknown whether antibodies against seasonal HCoV may cross-neutralize SARS-CoV-2. Data from neonates suggest that trans-placental antibodies against HCoV may have neutralizing capacity. Here we briefly review the epidemiologic observations on HCoV and discuss the potential implications for neutralizing and cross-neutralizing antibodies against SARS-CoV-2.